2002
DOI: 10.1093/hmg/11.12.1433
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for the XRCC2 R188H polymorphic site in DNA-damage repair and breast cancer

Abstract: An acquired genetic instability, resulting from the loss of some types of DNA repair, is an early event in the development of a subset of human cancers. The involvement of BRCA1 and BRCA2 in the homologous recombination repair (HRR) of double-strand breaks in DNA implicates this pathway in the suppression of breast cancer. A family of proteins related to human RAD51, including XRCC2, are essential components of this repair pathway. Using site-directed mutagenesis of XRCC2, we show that non-conservative substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 24 publications
8
72
4
Order By: Relevance
“…Frequencies of rare alleles were 0.41, 0.07, and 0.32 for XRCC3 241 Met, XRCC2 188 His, and NBS1 185 Gln, respectively, consistent with published reports (0.39, XRCC3; 0.06, XRCC2; and 0.32, NBS1) in European populations (8,12,14). All genotype distributions were in Hardy-Weinberg equilibrium.…”
Section: Resultssupporting
confidence: 89%
“…Frequencies of rare alleles were 0.41, 0.07, and 0.32 for XRCC3 241 Met, XRCC2 188 His, and NBS1 185 Gln, respectively, consistent with published reports (0.39, XRCC3; 0.06, XRCC2; and 0.32, NBS1) in European populations (8,12,14). All genotype distributions were in Hardy-Weinberg equilibrium.…”
Section: Resultssupporting
confidence: 89%
“…We 15,16 have previously described the design and methodology of this case control study. Briefly, recruitment commenced in November 1998 and is ongoing.…”
Section: Case-control Studymentioning
confidence: 99%
“…15,16 Briefly, the case and control groups were all female Caucasians. Table II shows the demographic characteristics of the population under study.…”
Section: Vegf Snps Haplotypes and Breast Cancer Susceptibility And Smentioning
confidence: 99%
“…Very recently, analyses of germline mutations of RAD51C in breast and ovarian cancer pedigrees have established this HR repair gene as a cancer susceptibility gene (18). A marginally significant association of breast cancer susceptibility has also been found with a rare variant of XRCC2 (19,20), as well as a potential link to ionizing radiation exposure (21). Earlier studies using Brca1 heterozygous knockout mice showed small increases in incidence of mammary tumors when Trp53 was also compromised, and this was further increased by irradiation (22).…”
Section: Discussionmentioning
confidence: 99%